FORMATION OF A MECHANISM FOR DIGITALIZATION AND ECOSYSTEM MODELING OF AGRO-INDUSTRIAL ENTERPRISES IN THE CONDITIONS OF THE CIRCULAR ECONOMY OF THE FUTURE - KNIAZIEVA, Olena; SHEVCHENKO, Valeriy; PETRENKO, Olga; OSYK, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of this article is to investigate the mechanism of integrating digital technologies into production and management processes, which will contribute not only to the restoration but also to the long-term competitiveness of the agro-industrial complex. The use of ecosystem modeling is significant, as it allows for considering enterprises not in isolation, but within agro-food clusters and regional value chains. This approach fosters synergy among producers, processors, scientific institutions, logistics structures, and government agencies. A conceptual model of ecosystem digitalization for agro-industrial complex enterprises is proposed, combining innovative agricultural management tools with mechanisms of inter-sectoral and inter-regional cooperation. An approach to assessing the effectiveness of agro-industrial complex digitalization is developed, based on a multi-criteria model that includes indicators of productivity, innovation, environmental sustainability, and social impact. It is substantiated that ecosystem modeling provides the opportunity to transition from recovery to regenerative development, where digital technologies act not only as an automation tool, but also as the basis for creating intelligent agri-food networks. A scientific and practical mechanism has been established that integrates digital transformation, quality management, and efficiency into the strategy for post-war development of agri-industrial enterprises. The study’s results can be utilized by managers of agro-industrial enterprises, IT specialists, and digital transformation consultants to implement innovative management tools. The proposed approaches will contribute to the development of a new management culture characterized by data transparency, digital models, dynamism, and flexibility in decision-making. In the context of military challenges and the destruction of production and logistics infrastructure, digitalization tools that enable optimized resource management, reduced transaction costs, and increased sustainability of agricultural enterprises are of particular importance.